The imperative for sensing innovations toward lab on cell in battery technology: a holistic survey of the emerging trend of embedding sensor technologies in electrochemical cells - Guillaume Thenaisie; Luis D. Couto (Discover Electronics)
Abstract The rapid evolution of battery technology has sparked an urgent need for advanced monitoring and diagnostic capabilities. This comprehensive review explores the emerging concept of Lab-on-Cell (LoC), a paradigm shift in battery management that integrates sophisticated sensing technologies directly into electrochemical cells. Through meticulous analysis, the study examines cutting-edge sensor technologies, including resistive and thermoelectric sensors, piezoelectric devices, electrochemical impedance spectroscopy, and optical fiber sensors. It delves into their principles, applications, and limitations within the context of battery diagnostics. Uniquely, this review intertwines technological assessment with geopolitical and economic context, charting the evolution of LoC technologies against a backdrop of global events and policy shifts. It sheds light on the complex drivers of innovation in this field, drawing connections between research trends, industrial needs, and regulatory changes. The study introduces a novel dual-reference system, separating general and LoC-specific sources to cater to a diverse readership. The review culminates in a forward-looking analysis of LoC technologies’ potential impact on battery management systems, cell design, and manufacturing processes. By weaving together technological advancements, market forces, and future projections, this in-depth examination provides a holistic view of the LoC landscape. It stands as a vital resource for researchers, industry professionals, and policymakers navigating the intricate future of energy storage technologies.